O ensino da Libras como segunda língua para os alunos ouvintes na educação básica do estado do Tocantins - Jesus, Kelly Cristina Fernandes de (Universidade Federal do Tocantins, 2023)
The course completion work entitled "The teaching of Libras as a second language for hearing students in basic education in the state of Tocantins" aims to portray the teaching of Libras as a second language and the performance of a deaf teacher in the school environment, in a Public School in the State of Tocantins located in the city of Palmas. The specific objective of this work deals with its implementation process in teaching from educational language policies. Reflections on the Brazilian Sign Language in different contexts will be presented. This research will follow a bibliographical study, through scientific articles, magazines and books, and also a documentary methodology following a qualitative approach. The final result of this research revealed that the Brazilian Sign Language can offer opportunities to the deaf and hearing people and even in the face of so many struggles and battles, movements and reprisals, the education of the deaf is still something that must be seen with more care, it requires changes, adaptations in educational institutions so that respect and learning can be exchanged in this space in an appropriate way.